Association between parents' education level and KIDMED index: a cross-sectional study. (20th October 2021) - Melis, A; Anastasia, A; Zannoner, A; Salussolia, A; De Dominicis, F; Arrichiello, F; Ferretti, F; Marini, S; Masini, A; Dallolio, L
Abstract: Background: Mediterranean diet (MD) is considered a healthy dietary model with several beneficial effects. A strict adherence to the MD in children, coupled with daily exercise, can prevent obesity and significantly reduce the risk of correlated chronic diseases, such metabolic syndrome. The aim of this study is to evaluate the association between parents' educational level and compliance to the MD in a convenience sample of Italian children. Methods: We conducted a cross-sectional study among 428 children aged 6-11 recruited in a primary school of Calderara di Reno (Italy) between May and June of 2017. Children's and parents' information were collected at baseline (i.e. age, BMI, occupation, educational level). A weekly food diary was administered to evaluate the participant's dietary habits. The degree of adherence to MD was derived from these diaries using the KIDMED index developed in 2003 by Serra-Majem et al. We used multiple linear regression models, adjusted for age and gender, to investigate how parents' educational level affected children's KIDMED index. Results: Adherence to the MD was high, medium and poor in, respectively, 4%, 60% and 36% of children. Higher prevalence of overweight and obesity was observed among those with lower adherence to the MD. The linear regression model shows that fathers' educational level is not associated to children's KIDMED index variation. On the other hand, a higher mothers' educational level is linked to an increased weekly KIDMED index (p = 0.012) as well as an increased weekend KIDMED index (p = 0.048). Conclusions: Mothers' education level is associated with increased adherence to MD, both weekly and weekend. The greater difference has been observed during weekend, when children of highly educated mothers score higher at KIDMED index. Key messages: Mothers' educational level plays an important role in children's eating habits, with higher educational level associated with a better adherence to the MD. It is critical to implement parents' toolkit to promote healthy dietary patterns and adherence to MD in order to correct these social differences.